1998
DOI: 10.1046/j.1440-1819.1998.00405.x
|View full text |Cite
|
Sign up to set email alerts
|

The increasing use of anticonvulsants in prophylactic treatment of bipolar disorder

Abstract: Key wordsThe medical records of patients with bipolar disorders who received prophylactic drug treatments during three time periods from January 1983 to December 1984. January 1988 to December 1989, and from January 1993 to December 1994. were reviewed retrospectively. The percentage of lithium monotherapy sharply decreased from 96% (51/53) in the first study period to 51.9% (83/160) in the third study period. Carbamazepine monotherapy and combination of lithium and carbamazepine increased from 3.8% in the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 14 publications
(13 reference statements)
0
4
0
Order By: Relevance
“…Although there are now several available mood stabilizers, 1 lithium is still the drug of first choice for maintenance treatment for bipolar disorder. 2 However, lithium is not effective for all bipolar patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there are now several available mood stabilizers, 1 lithium is still the drug of first choice for maintenance treatment for bipolar disorder. 2 However, lithium is not effective for all bipolar patients.…”
Section: Introductionmentioning
confidence: 99%
“…Bipolar disorder is a socially disabling mental disorder that affects approximately 1% of the population. Although there are now several available mood stabilizers, 1 lithium is still the drug of first choice for maintenance treatment for bipolar disorder. 2 However, lithium is not effective for all bipolar patients.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it was found to be compatible with lithium in the treatment of acute mania in small-scale trials [9,10]. In Taiwan, CBZ has been increasingly used to treat bipolar disorder [11]. Its efficacy for treating acute mania was recently reconfirmed following the completion of large-scale, randomized, placebo-controlled trials in North America using extended-release CBZ [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Women with epilepsy typically require ongoing AED therapy during pregnancy to avoid the potentially adverse effects of seizures on themselves or the developing fetus. AEDs, however, also are used to treat other illnesses, including migraines, chronic pain, and bipolar disorder [Yang et al, 1998; Russo et al, 2002; Pennell, 2004; Grunze, 2008, 2010; Newport et al, 2008; Bowden, 2009; Bramness et al, 2009; Reimers, 2009; Moch, 2010; Wisner et al, 2011]. Some have suggested that considering AED use among only those with epilepsy would underestimate total use by approximately 50% [Pennell, 2004].…”
Section: Introductionmentioning
confidence: 99%